INTELLECTUAL PROPERTY AS A TOOL FOR THE DEVELOPMENT OF BIOTECHNOLOGY IN PHARMACY: AN EDUCATIONAL APPROACH - Zaitseva, Galyna; Gozhdzinsky, Sergii; Pushkareva, Yaroslava (Sworld-Us Conference proceedings, 2025)
The article examines intellectual property as a key factor in the development of biotechnology in pharmacy, with a special emphasis on the educational dimension of professional training. The structure of the course “Intellectual Property and Patent Studie